(untitled) (Hekima Review, 2005)
Peter Edmonds is a Jesuit priest from England and member of the Jesuit Province of Zimbabwe. He studied the Bible at the Biblical Institute in Rome. Afterwards, he has dedicated his life as a priest to promoting the biblical apostolate in Zimbabwe and teaching Scripture, mainly the New Testament, first in the Regional Seminary in Zimbabwe, and then, at Hekima College, the Jesuit College of Theology.